A map of brain neuropils and fiber systems in the ant Cardiocondyla obscurior - Bressan, Joris M. A.; Benz, Martin; Oettler, Jan; Heinze, Jürgen; Hartenstein, Volker; Sprecher, Simon G. (Frontiers in Neuroanatomy, 2015)
A wide spectrum of occupied ecological niches and spectacular morphological adaptations make social insects a prime object for comparative neuroanatomical studies. Eusocial insects have evolved complex societies based on caste polyphenism. A diverse behavioral repertoire of morphologically distinct castes of the same species requires a high degree of plasticity in the central nervous system. We have analyzed the central brain neuropils and fiber tract systems of the worker of the ant Cardiocondyla obscurior, a model for the study of social traits. Our analysis is based on whole mount preparations of adult brains labeled with an antibody against Drosophila-Synapsin, which cross-reacts strongly with synapses in Cardiocondyla. Neuropil compartments stand out as domains with a certain texture and intensity of the anti-Synapsin signal. By contrast, fiber tracts, which are composed of bundles of axons accompanied by glia and are devoid of synapses, appear as channels or sheaths with low anti-Synapsin signal. We have generated a digital 3D atlas of the Cardiocondyla brain neuropil. The atlas provides a reference for future studies of brain polymorphisms in distinct castes, brain development or localization of neurotransmitter systems.